Global efforts to combat smoking : an economic evaluation of smoking control policies - Goel, Rajeev K., 1962- (Ashgate Pub. Co., 2008)
This book brings together the findings of economists on the effectiveness of price and non-price policy initiatives to combat smoking and draws conclusions regarding the efficacy of the various policy measures. The book will be essential reading for policy makers, health practitioners and researchers in health economics.